Grey relational analysis to identify the ideal combination of impact toughness and hardness for biodegradable quenched-tempered 42CrMo4 steel - Bhagya Laxmi; Jayashree P K; Sathish Rao U; Ananda Hegde; Sathyashankara Sharma (Materials Research Express)
This work investigated the effect of different types of tempering on the hardness, impact toughness and microstructure of normalized and biodegradable-quenched 42CrMo4 steel. Specimens were normalised initially then hardened using green oil quenchants such as Pinnay oil, Karanja seed oil and blended oil (Equal volume percentage of Pinnay and Karanja seed oil) then subjected to single stage tempering process. Surface response methodology was used to obtain optimised conditions from single stage tempering process to carry out other types of the tempering processes such as multiple and step tempering processes. Grey relational analysis was used to select the tempering process that yield best balanced property condition. The two steps tempering process with hardness of 36 HRC, impact toughness of 56 Joules and with grey relational grade of 0.7 was considered as the process to get optimal mix of hardness and impact toughness in 42CrMo4 steel.